Literary magazines, magazines of literature: at crossroads (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This paper is a reflection about periodical publications on culture and literature. It examines several examples that illustrate how difficult it is to draw a boundary between scientific journals and literary creation. Though it seems to be a clear difference between both categories, the examination of real magazines, reviews and journals demonstrate that this boundary is only useful in extreme cases, and that the nature of literature itself makes it impossible to separate creation from research.
Keywords: cultural press; literary magazines; journals of literature; indexed journals in humanities; scientific journals in humanities